Preparation of Solid Soap with Lemongrass (Cymbopogon citratus) Extractby Cold Process - Nafira Alfi Zaini Amrillah; Aster Rahayu; Siti Jamilatun; Nuraini Nuraini; Sely Anggi Oktavian; Nurul Isnaini (Universitas Darussalam Gontor, 2023)
Soap cannot be separated from human life, because soap is always needed to remove dirt that sticks to the surface of human skin. Soap has properties that can produce foam, cleanser, and is alkaline. If the alkaline properties are too high, it can cause irritation to humans which is characterized by thin peeling of the skin. So it is necessary to innovate home soaps that are safer for the skin. Lemongrass isa plant that has an antibacterial content when combined with soap. In this study, the process of making soap was carried out simply using the clod process method without heating using citronella extract as a source of antibacterial. The soap composition will be optimized in order to produce good quality soap based on pH value, free fatty acids, organoleptic tests (odor, color, hardness, softness, foam) and saponification rate. The results of this optimization show that the soap that has a good appearance and texture is a soap that has a ratio of cooking oil and olive oil of 90:10 with a total mass of 55 grams of oil and a concentration of 64.8% NaOH solution, as well as levels of free fatty acids, pH and saponification number respectively 0.33 %, 9, 18.085 mg/g.